Perancangan Interior Marine Science Center di Surabaya - Forester, Kevin (Intra, 2013)
Marine Science Center is a place where people can get various information about the sea, learn and recreation with the family. The main function of the Marine Science Centre is to invite the people to know, to keep, and to conserve the sea and everything on it, to remember that ocean is a very potential resources and we need to preserve it. Some supporting literature are used, like layout planning, air circulation, lighting, and another related elements to achieve an optimal design, in order to attract visitors and the function from the Marine Science Center can be succeed.